Effect of Nitrogen and Molybdenum on the Growth and Yield of Garden Pea (Pisum sativum L.) - Rabbi, A. K. M. Z.; Paul, A. K.; Sarker, J. R. (International Journal of Bio-resource and Stress Management, 2011)
A field experiment was conducted at the research farm of Sher-e-Bangla Agricultural University, Dhaka, during December 2006 to February 2007 to study the effect of nitrogen and molybdenum on the growth and yield of garden pea. The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications of each treatment. There were 15 treatments combinations in the experiment comprising 5 levels of N (0, 30, 60, 90 & 120 kg ha-1 designated as N0, N30, N60, N90 & N120 respectively) and 3 levels of Mo (0, 0.4 & 0.8 kg ha-1 designated as Mo0, Mo0.4& Mo0.8 respectively). The individual and interaction effect of N and Mo on growth and yield was found significant. Nitrogen @ 90 kg ha-1 gave the highest number of branches plant-1, highest number of pods plant-1, highest pod length, highest green and mature seed weight 10 pods-1, highest green and mature pod yield but maximum plant height and number of seeds pod-1 were found under 120 kg N ha-1. In case of molybdenum application the highest plant height, highest number of branches plant-1, highest pod length, highest seed weight 10 pods-1 were recorded in 0.4 kg Mo ha-1. Molybdenum @ 0.8 kg ha-1 gave the highest fresh weight of plant and highest fresh weight of pods. The treatment combination of N120 Mo0.4 produce the maximum plant height, highest number of seed pod-1, highest number of pods plant-1, highest fresh weight of plant, but the treatment N90 Mo0.4 gave the maximum number of branches plant-1, highest length of pod, highest number of seeds pod-1, highest seed weight 10 pods-1, highest pod yield, maximum P, K and S content in plants. Lowest N, P, K and S content was found in control (N0Mo0) treatment. From the present findings it can be concluded that application of N @ 90 g ha-1 along with Mo @ 0.4 kg ha-1 is the most suitable combination to achieve the maximum return from garden pea plants.